BIOSORPSI Cr(III) PADA BIOSORBEN SERAT SABUT KELAPA HIJAU TERAMOBILISASI EDTA - Sudiarta, I Wayan; Dwijani Sulihingtyas, Wahyu (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012, 2012)
Studies on biosorption of Cr(III) on coconut fiber immobilized with EDTA biosorbent (B-EDTA) have been conducted. These studies included the optimization of EDTA immobilization on biosorbent, optimization of Cr(III) biosorption on B-EDTA biosorbent that include pH dan contact time biosorption, and also studied the mechanisms of Cr(III) interactions on biosorbent B-EDTA by squential desorption. The result showed that the optimum EDTA immobilization on biosorbent E-EDTA occured at ratio of 1mmol EDTA : 4g biosorbet (0,25mmol/g ), with the surface acidity of biosorbent B-EDTA of 2,18 mmol/g. Optimum biosorption process of Cr(III) on biosorbent B-EDTA occured at pH = 3, contact time of 120 minutes, with the biosorption capacity of Cr(III) on biosorbent B-EDTA of 8,32 mg/g. The squential desorption studies show that the interaction of Cr(III) on biosorbent B-EDTA occured predominantly through physical adsorption namely Van der Waals bonding.
Keywords: biosorption, immobilization, EDTA, Cr(III)